Student leadership at the university : an explanatory model - CÁCERES RECHE, MARÍA PILAR (2011)
The exercise of leadership in the educational area and its diverse forms of being reflected in practice continue to arouse interest at the time of designing and developing research that reveals the characteristics that a leader must have in order to be considered a competent university leader, that is, a college student who carries out activities and a leadership position on his or her campus. In this sense, the present work aims to analyze the profile of the student leader to generate an explanatory model, being answered by means of a series of questions. Next, a cross-sectional study of university students at the University of Santo Tomás is carried out, obtaining statistical-descriptive data that indicate the mean scores in relation to each of the dimensions of the sociodemographic factors of this research. In addition, gender and age are identified as study factors that coincide with other research, as well as the qualities, expectations and formation of the student leader. In the present study, female gender is significant in relation to leadership practice, and age does not show significant differences between the groups. Finally, it is concluded by determining as key the role of students who exercise leadership in the University. In addition, it should be noted that the present research is derived from the Doctoral Thesis entitled: “Student leadership at the University Santo Tomás de Bucaramanga: Pedagogical proposal”, defended at the University of Granada, Spain. Funded by Proyecto de investigación, Colombia. Code: 2008/12058.